Education in Disaster Situations: The Impact of The Kahramanmaraş Earthquake on Teachers' Experiences - Memet Kuzey; Ekrem Cengiz; Hasan Bozkaya; Faruk Arıcı (Sakarya University Journal of Education)
This study examines how the earthquake that occurred on February 6, 2023, in Kahramanmaraş, Turkey, has affected educational activities in the region. The research utilized questionnaires to survey teachers and gather information about the main problems they experienced after the earthquake and their solution suggestions. The findings provide valuable insights for educators and policymakers to tackle the challenges teachers and students face after a natural disaster. The study employed a basic qualitative research design within qualitative research methods. The study group comprised 42 volunteer teachers from eleven different Turkish provinces at various education levels who experienced the February 6, 2023, earthquake centered in Kahramanmaraş and participated in educational activities in the same area following the earthquake. The group of research participants was selected through easily accessible case sampling, one of the types of purposeful sampling. The data collected underwent content analysis. As per the study results, teachers detected issues that have arisen after the earthquake in the realms of educational infrastructure, psychosocial well-being, security, communication, and other factors. They then devised individual and collaborative solutions to address these challenges. Additionally, the study discussed the proposed solutions of teachers for addressing the psychosocial issues that students face in the aftermath of an earthquake. It provides crucial insights for comprehending the problems in post-earthquake education and extending support to students. Teachers' recommendations for enhancing earthquake education and awareness can significantly aid future preparedness and crisis management.